Emisi Dinitrogen Oksida (N2O) pada Beberapa Metode Pengelolaan Limbah Sawah di Kecamatan Anjir - Sylvi Riska Amalia; Abdul Hadi; Meldia Septiana (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Wetlands have unique biodiversity and natural phenomena. The climate has recently changed rapidly due to greenhouse gas emissions, especially nitrous oxide from human activities such as paddy rice farming. The purpose of this study is to determine the effect of rice field waste management on the population of nitrogen-fixing bacteria and N2O emissions, and as to determine the shape and closeness of the relationship between the population of nitrogen-fixing bacteria and N2O emissions with different waste management methods. The research method used is a one-factor RGD. Close chamber technique is used for N2O emmisions analysis. The factor tested was the method of managing paddy waste before rice planting with five treatments, namely: A = Rice field waste was slashed and then lifted into the mound after a few days of being returned to the field; B = Rice field waste is carried out management slashed, rolled up, reversed and stretched; C = Rice field waste is slashed, planted with traces and then slashed again after the trace is transferred to land outside the research plot; D = Rice field waste sprayed with herbicide 2 times; E = Rice field waste sprayed with herbicide 1 time and then soil in the tractor. Each treatment was repeated four times so that 20 units of the experiment were obtained. The results showed that the method of rice field waste management carried out had no real effect on N2O emissions and nitrogen-fixing bacteria. N2O emissions not correlate with the activity of nitrogen-fixing bacteria from several methods of rice field waste management carried out